EL VOCABULARIO EN LA ENSEÑANZA TRADICIONAL DEL LATÍN: PROBLEMAS Y PROPUESTAS | VOCABULARY IN THE TRADITIONAL TEACHING OF LATIN: PROBLEMS AND PROPOSALS - Meynet, Beatriz Carina (Estudos Linguísticos e Literários, 2016)
La enseñanza del vocabulario desde el método tradicional presenta serios problemas: 1) no se considera un contenido importante; 2) su introducción a partir del aprendizaje de declinaciones y conjugaciones afecta a la calidad de los ítems seleccionados; 3) la desatención a la información argumental de los verbos afecta al aprendizaje de los casos. Nuestro objetivo es proponer soluciones a dichos problemas a partir de criterios lingüísticos (semánticos y sintácticos) y estadísticos (frecuencia). Abstract: The teaching of vocabulary with a traditional approach presents serious problems: 1) vocabulary is not considered to be an important subject; 2) the teaching of vocabulary based upon the learning of declensions and conjugations affects the appropriateness of the words selected; 3) and the lack of attention to the argument structure of selected verbs affects the learning of the case system. The aim of this study is to provide some solutions to these problems by proposing linguistic (semantic and syntactic) and statistical (frequency) criteria.